KORELASI KINERJA PENYULUH PERTANIAN DENGAN KAPASITAS PETANI PADI SAWAH DI DESA WONUA HOA KECAMATAN LAMBUYA KABUPATEN KONAWE - Lepriana Oktoberlita; Musaddar Musaddar; Sukmawati Abdullah (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2024)
This paper aims to determine the relationship between the performance of agricultural extension workers and the capacity of farmers in rice farming in Wonua Hoa Village, Lambuya District, Konawe Regency. This research is also motivated by the number of rice farmers in each group as many as 125 farmers in 2023, for the number of farmer groups themselves as many as 5 rice farmer groups. This number was obtained from data from the Lambuya District Agricultural Extension Center. In addition, the performance of the Lambuya BPP is also suspected of having a relationship with the number of rice farmers in the area. Therefore, fellow farmers in improving their farming efforts are very dependent on the performance of Agricultural Extension Workers who directly provide training to farmers on their farms. So that the total respondents used in this study were 56 people. This study used quantitative analysis methods, namely surveys, interviews, library methods using questionnaires and documentation. The data collected using questionnaires were then processed using SPSS for window version 22. The data analysis techniques used were the Class Interval formula and the Spearman Rank Correlation formula. The results of the study indicate that the performance of agricultural extension workers in Wonua Hoa Village has a very strong and significantly positive correlation coefficient category with farmer capacity. This means that the better the performance of agricultural extension workers, the better the capacity of rice farmers in Wonua Hoa Village.